Mobile Banking Service Quality and Customer Relationship Quality in Indonesian Islamic Banks: The Moderating Effect of Gender - Kirana, Laras Puspa; Komaladewi, Rita; Oesman, Yevis Marty (Economics and Business Journal (ECBIS), 2025)
This study aims to analyze the impact of mobile banking service quality on customer relationship quality in Indonesian Islamic banks, with a focus on the moderating role of gender. With the rapid growth of digital technology, mobile banking has become a crucial factor influencing customer experience, particularly within the context of Islamic banking, which operates on Islamic principles. This research investigates how the quality of mobile banking services (such as ease of access, security, and transaction convenience) affects customer relationship quality (including trust, satisfaction, and loyalty). Additionally, it explores whether gender moderates the relationship between mobile banking service quality and customer relationship quality. Data were collected through surveys from customers of Indonesian Islamic banks, and the analysis was conducted using Structural Equation Modeling (SEM). The findings are expected to provide insights into the design of mobile banking services that are responsive to gender-specific needs and offer recommendations for Islamic banks to strengthen customer relationships through more inclusive digital innovations.